INDUCTION OF STERILITY IN THE UZI FLY, EXORISTABOMBYCIS (LOUIS) (DIPTERA: TACHINIDAE) THROUGH GAMMA IRRADIATION OF PUPAE - KATIYAR, R. L.; MANJUNATH, D.; PRASAD, K. SATHYA; KISHORE, RAM; DATTA, R. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
Four, five, six and seven day old male and female pupae of Exorista bombycis were subjected to a predetermined dose of 2 Kr gamma radiation. Adult emergence declined significantly in 4 and 5-day old irradiated pupae compared to control. Average life span of adults emerging from 5 day-old irradiated pupae decreased significantly when compared with control. There was no significant variation in the period of survival between the male and female flies emerging from normal and irradiated pupae. Fecundity of normal females mated with sterile males emerged from irradiated pupae was not significantly different from control, but the same in females emerging from 5, 6 and 7-day old irradiated pupae was significantly lower when they mated with normal males. No egg laying was recorded in the females emerging from 5 and 6 day-old irradiated pupae as the ovarian development was completely inhibited. The radiation dose (2 Kr), which induced total sterility in males and females, did not affect the mating ability of males and receptivity of females. Under field release programme of the irradiated flies in a limited area, a ratio of 10:1:1 (sterile male:normal male:normal female) was found effective in suppressing the progeny of E. bombycis.